Prevalence of joint, entheseal, tendon, and bursal findings in young, healthy individuals by musculoskeletal ultrasound. (2nd January 2023) - Schreiner, JK; Scheicht, D; Karakostas, P; Recker, F; Ziob, J; Behning, C; Preuss, P; Brossart, P; Schäfer, VS
Abstract : Objective: The purpose of this study was to determine the prevalence of joint, enthesis, bursa, and tendon ultrasound findings in large and medium joints of young, healthy individuals. Method: Ultrasound assessment of large and medium joints, bursae, tendons, and entheses was performed in healthy individuals below the age of 30 years. Participants also underwent bioelectrical impedance analysis and conducted supervised weight training to determine maximum strength. The prevalence of ultrasound findings was calculated and a binary logistic regression model was applied to evaluate factors associated with the present findings. Results: Fifty-one healthy individuals (52.9% female) with a mean age of 23.7 years were included in this study. Joint effusion in at least one joint was observed in 72.6% of the individuals (n = 37) and entheseal pathology in at least one enthesis was detected in 27.5% (n = 14). A binary logistic regression model indicated a significant association between reported hours of sports activity per week and the prevalence of effusion in the knee (p = 0.017). In addition, associations were observed between entheseal pathology in at least one entheseal site and body mass index (BMI) (p = 0.015) as well as fat mass index (p = 0.026). Conclusion: Joint effusion in large and medium joints, as well as entheseal hyperperfusion, bursal effusion, and tendon sheath effusion, are found in healthy individuals. Hours of sports activity per week, BMI and fat mass index showed significant associations with the findings in joints and entheses.